Journeying Towards Transformative Mathematics Teacher through Critical Self-Reflection - Dhungana, Hem Lal (Academic Journal of Mathematics Education, 2023)
In this autoethnographic study, I have critically explored my past experiences as a student, teacher, and educational researcher. This study shows my transformation from a traditional practitioner to a critical and culturally responsive mathematics teacher. The main purpose of this study is to portray the episode of critical self-reflection on my experiences of engaging mathematical activities, aiming at improving my practices as a teacher, practitioner-researcher and an educator by exploring students’ mathematical ideas constructed through de/contextual teaching. Through this autoethnographic research, I have critically reflected upon my experience and I explored the possible ways of using cultural heritage that is contextualized in mathematics class. To analyze critically the narratives, I employed three theories: living education theory, sociocultural theory and, transformative theory. I positioned myself as a ontology, is multiple subjective realities. I am guided three paradigms such as interpretivism, criticalism and postmodern research paradigms. During this study, I came to realize that culturally decontextualized mathematics education is not able to encourage teachers to implement empowering mathematics pedagogy in meaningful learning of mathematics. In addition, transformative learning plays a vital role in learning mathematics by through contextual teaching and learning in which constructivist and precarious viewpoints empower both teachers and students to observe their views and values to build knowledge through critical self-reflection.